2001
DOI: 10.1097/00007435-200101000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Prevalence of Chlamydia, Herpes, and Viral Hepatitis in a Homeless Adolescent Population

Abstract: Among females, the incidence of herpes simplex virus type 2 (> 25%) and C trachomatis (12%) was relatively high. Inconsistent condom use was the primary factor associated with a significantly greater risk of incident sexually transmitted infections. This was especially true for females with multiple partners. Homeless adolescents also are at high risk for hepatitis B virus and hepatitis C virus infection, primarily associated with self-reported injection drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 24 publications
6
62
1
Order By: Relevance
“…However, one constant found among all street youth is their precarious living conditions, which include poverty, residential instability and emotional and psychological vulnerability. 2,5 These conditions may lead to behaviour that expose street youth to STIs and blood-borne infections, substance use and abuse.…”
Section: Street Youthmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one constant found among all street youth is their precarious living conditions, which include poverty, residential instability and emotional and psychological vulnerability. 2,5 These conditions may lead to behaviour that expose street youth to STIs and blood-borne infections, substance use and abuse.…”
Section: Street Youthmentioning
confidence: 99%
“…[11][12][13] The prevalence (overall cases) and incidence (new cases) rates of many STIs and blood-borne infections are reported to be 10 to 12 times higher in street youth than in youth of the same age group among the general population. 5 A study on street youth in Montréal found that almost one-half (45.8%) had injected drugs. Street youth were also found to be 11 times more likely to die of drug overdose and suicide 15 than general population youth.…”
Section: Canadian Street Youth: a Vulnerable Populationmentioning
confidence: 99%
“…Elimination of HBV infection in our population would require universal immunization. Given the high prevalence of HBV infection in streetinvolved youth 10,11,14 and their relatively low level of immunity, efforts to improve HBV vaccine coverage in street-involved youth is important. The primary challenge in the prevention and control of HBV infection in this population is to enhance access to health care given their mobility.…”
Section: Vaccine-induced Immunity To Hepatitis B Among Canadian Streementioning
confidence: 99%
“…These social and contextual factors may also place them at higher risk for practices that are associated with the transmission of sexually transmitted blood-borne infections (STBBIs), including HBV. 10,11 Furthermore, since effective immunization against HBV requires at least two consecutive vaccinations over the course of 6 months, it is often difficult to complete the full vaccination schedule for this hard-to-reach population at high risk for HBV infection. While several studies suggest that the prevalence of HBV infection is more than ten times higher among street-involved youth than that observed in general youth population, 10,11,14 few studies have focused on the proportion of having vaccine-induced immunity to HBV in this population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation